2005
DOI: 10.1017/s0266467405002725
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the quality of a tropical ripe fruit and the response of three frugivores

Abstract: Seasonality in tropical forests can be more subtle than that of temperate forests but still affects the resources available to wildlife. Much work has been done describing changes in fruit availability and dietary composition but the nutritional quality of any particular food item is assumed to be relatively constant. We investigated seasonal changes in the quality of the ripe fruit of Celtis durandii, a common tree that produces fruit year-round and is important in the diets of many species. The lipid content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…There is limited available data on how both nutrient requirements and nutrient consumption influence gut microbial composition and function within a single population of animals. Although we did not measure actual nutrient consumption and there are no published data for other foods consumed by individuals in our population, many authors have reported significant differences in the lipids, protein, sugars, complex polysaccharides, and chitin content of invertebrates and fruits eaten by primates, both between and within taxa (Bell, ; Chapman et al, ; Chivers, ; Houle, Chapman, & Vickery, ; O'Driscoll Worman & Chapman, ; Raubenheimer & Rothman, ; Rothman et al, ). Even though we found relationships between the nutrient content of some fruits and gut microbial function, this does not represent a complete picture of how variation in macronutrient consumption influences white‐faced capuchin gut microbial community structure and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited available data on how both nutrient requirements and nutrient consumption influence gut microbial composition and function within a single population of animals. Although we did not measure actual nutrient consumption and there are no published data for other foods consumed by individuals in our population, many authors have reported significant differences in the lipids, protein, sugars, complex polysaccharides, and chitin content of invertebrates and fruits eaten by primates, both between and within taxa (Bell, ; Chapman et al, ; Chivers, ; Houle, Chapman, & Vickery, ; O'Driscoll Worman & Chapman, ; Raubenheimer & Rothman, ; Rothman et al, ). Even though we found relationships between the nutrient content of some fruits and gut microbial function, this does not represent a complete picture of how variation in macronutrient consumption influences white‐faced capuchin gut microbial community structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, an individual's diet can undergo major shifts both in which types of food items are eaten (e.g., fruits, leaves, arthropods), and in which taxa of those food types are eaten over the course of days, weeks, and months (Chapman, Chapman, Rode, Hauck, & Mcdowell, ). In addition, given that fruits and insects vary in the amount of lipids, protein, sugars, complex polysaccharides, and chitin they contain, both between and within taxa, nutrient mixing is required for hosts to obtain a nutritionally adequate diet (Bell, ; Chapman et al, ; Chivers, ; O'Driscoll Worman & Chapman, ; Raubenheimer & Rothman, ; Rothman, Dierenfeld, Hintz, & Pell, ). Recent studies, both in primates and other mammals, indicate that the gut microbiota buffers these dietary changes by increasing the bacterial production of short‐chain fatty acids and other molecules that then can be used by the host for energy during periods of nutritional shortfalls (Amato, ; Amato et al, ; Gomez et al, ; Schnorr et al, ; Smits et al, ; Sun et al, ; Tremaroli & Bäckhed, ).…”
Section: Introductionmentioning
confidence: 99%
“…Kanyawara is located in the northwestern part of Kibale National Park (0°13′–0°41′N, 30°19′–30°32′E) in Uganda, at about 1,500 m elevation [Wrangham et al, ]. This mature, mid‐altitude semi‐deciduous and evergreen ecotype has swamp, primary, and regenerating forest that was logged pre‐1992 [O'Driscoll Worman & Chapman, ]. Dominant trees in unlogged areas are Parinari excelsa , Celtis gomphophylla , and Markhamia lutea [Sekercioglu, ], while the woody shrub Acanthus polystachius dominates previously logged areas [Osborne et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Kanyawara is located in the northwest of Kibale National Park (0°13′–0°41′N, 30°19′–30°32′E), Uganda, at an elevation of about 1500 m (Wrangham et al, ). This mature, mid‐altitude, semideciduous, and evergreen ecotype has primary, swamp and regenerating forest logged pre‐1992 (O'Driscoll Worman & Chapman, ). Gaps in canopy cover therefore, have arisen from past logging activities, but have also been naturally cleared by elephants ( Loxodonta africana ) found within the national park.…”
Section: Methodsmentioning
confidence: 99%